Parental status in later life and parents' risk of cognitive impairment - Yan Zhang; Jason Fletcher (Elsevier, 2021)
Parental status can influence parents' well-being in significant ways, but little research has examined its impact on older adults' cognitive health in the U.S. Using data from the National Health and Aging Trends Study (NHATS) 2011-2019, this study examines whether parental status is related to the risk of cognitive impairment among older adults in the U.S. We found that the presence of adult children (i.e., having at least one living adult child) was associated with a lower risk of cognitive impairment for older parents. Moreover, compared to childless older adults, older parents who had three and more children, who had adult daughter(s), and who had biological/adopted adult children displayed a significantly lower risk of cognitive impairment. This study highlights the importance of adult children as resources of support and caring that may benefit older parents' cognitive health. The findings can help to identify the most vulnerable subpopulations among aging adults so that medical workers and policy makers can design effective strategies to protect cognitive function for those "at risk" older adults.